Thailand Trapped: Catch-up Legacies and Contemporary Malaise. Issue 2 (11th July 2018) - Kanchoochat, Veerayooth
Abstract: A better understanding of Thailand's contemporary malaise needs a perspective that combines political and economic aspects without losing sight of history. This article applies the concept of path dependence to examine how pre-1997 catch-up industrialisation shaped the post-crisis trajectory. It argues that the catch-up process has left a number of important legacies, especially the symbiotic relationship between the military, banking conglomerates, and technocrats; dominant growth narrative with a focus on macroeconomic stability; and overly centralised and bloated state structures. These legacies have shaped the strategies and legitimacies of today's political actors and rendered the pursuit of growth increasingly contradictory to maintaining order.